PERANCANGAN GAME PUZZLE HURUF HIJAIYAH MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Gelen Jeniffer; Tri Ferga Prasetyo (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Hijaiyyah (Arabic letters) has been around for centuries, when the Al-Quran was first revealed using hijaiyyah, because the first time the Al-Quran was revealed was in Arabic. The importance of learning Arabic letters because these letters are used in writing the Koran. Muslims are obligated to learn the Koran. Educational games are a type of media that are used to teach, increase user knowledge through unique and interesting media. This type is usually intended for children. Construct 2 is a game creator made by Scirra, which is one of the games that game developers are interested in because construct 2 is easy to use and has many tutorials and templates available. in making this game the author uses the Game Development Life Cycle (GDLC) method because the stages are appropriate. The purpose of this research is to introduce the basic knowledge of Islamic religion, produce games with interactive 2D views and features that are interesting for players, this educational game is to encourage children to be more active in learning.